Religion and politics in the 21st century : global and local reflections - Vlas, Natalia; Boari, Vasile (Cambridge Scholars Publishing, 2013)
Religion and Politics in the 21st Century is composed of a number of articles that were presented during the 2012 international conference on ""Religion and Politics in the Globalization Era"" organized by the Centre for Political Analysis in Cluj-Napoca, Romania. With careful attention given to 21st century religious resurgence and its dynamic interactions with political structures and the public sphere, the present volume captures a wide variety of perspectives on contemporary religion and p ...